RELATIONSHIP BETWEEN STRESS FACTORS AND GASTRITIS IN STUDENTS OF PRIMA INDONESIA UNIVERCITY - Clinton Antony; Christine Christine; Suhartina Suhartina; Sri Lestari Ramadhani Nasution (Universitas Negeri Gorontalo, 2022)
Gatritis is the inflammation or swelling of gastric mucose triggered by an irritation and infection. Gatritis occurs if it solely causes simple gastric inflammation, else gastric ulcers happen when the acidity damages stomach lining. Based on one of Indonesia's health profile in 2016, gastritis is top 10 of the most in-hospital patients numbering 380.744 cases recorded. It is known that gastritis risk factors include long-term stress that often encountered in university students, stimulates high-amount gastric acid production; Objective: The main ocassion of this study was to rule out the link between stress and gastritis recurrences in undergarduate at Faculty of Medicine, Universitas Prima Indonesia; Method: This testing utilize descriptive-analytic-observational method with cross-sectional design. We used a total of 94 respondents, all of them are currently stated as active students of 2020/2021at Faculty of Medicine, Universitas Prima Indonesia; Result: Statistics were gathered by respondents filling in some questionnaires, hence being analyzed using Chi-Square, which shows 37 people (39.4%) are suffering recurrence aastritis and the other 57 people 60.6%) are not; Conclusion: Therefore, we concluded that there is a intense connection between stress and gastritis recurrences with p=0.001 (p0.05) where the more stress a person received, the more probable he/she is getting gastritis recurrences